Developing Bioengineered 3D-Printed Composite Scaffolds with Antimicrobial Potential for Bone Tissue Regeneration - Andreea Trifan; Eduard Liciu; Cristina Busuioc; Izabela-Cristina Stancu; Adela Banciu; Carmen Nicolae; Mihai Dragomir; Doru-Daniel Cristea; Rosina-Elena Sabău; David-Andrei Nițulescu; Alexandru Paraschiv (Journal of Functional Biomaterials, 2025)
This research activity proposes to produce composite hydrogel–bioactive glass. The primary purpose of this research is to develop and optimize 3D-printed scaffolds using doped bioglass, aimed at enhancing bone regeneration in bone defects. The bioglass, a bioactive material known for its bone-bonding ability (SiO2–P2O5–CaO–Na2O), co-doped with europium and silver was synthesized and doped to improve its biological properties. This doped bioglass was then combined with a biocompatible hydrogel, chosen for its adequate cellular response and printability. The composite material was printed to form a scaffold, providing a structure that not only supports the damaged bone but also encourages osteogenesis. A variety of methods were employed to assess the rheological, compositional, and morphological characteristics of the samples: Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) coupled with energy-dispersive X-ray spectroscopy (EDS). Additionally, simulated body fluid (SBF) immersion for bioactivity monitoring and immunocytochemistry for cell viability were used to evaluate the biological response of the scaffolds.